New aspects of cheap food - Keller, Rudolph (Research Books Limited, in association with William Heinemann (Medical Books) Limited, 1943)
New Aspects of Cheap Food presents a Central European view of the nutritional aspects of cheap food. It covers foods such as vegetables, milk, sweetening, beverages, salt, and potassium. It also considers the food of soldiers and the economic aspects of cheap and scientific feeding.